ANALYSIS OF MATHEMATICAL REFLECTIVE THINKING ABILITY IN THE MATERIAL OF ALGEBRA BASED ON GENDER - Hikmafadlia, Isti; Utami, Nida Sri (Universitas Tanjungpura, 2025)
Reflective thinking comprising Techniques, Monitoring, Insight, and Conceptualization stages, plays a crucial role in students